Rancang Bangun Sistem E-Commerce menggunakan Aplikasi Content Management System OpenCart Untuk Meningkatkan Penjualan (Studi kasus pada DnD Collection) - Ferdinandus Lidang Witi; YosepD.DaYenKhwuta (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
DnD Collection is a store located in the city of Ende, Ende district, East Nusa Tenggara province. In their daily life, this shop is engaged in the business of buying and selling laptops, computers and clothing or fashion. When faced with the COVID-19 pandemic, sales experienced a drastic decline because the sales system was still conventional. To overcome this problem, the author conducts research by building an e-commerce system that uses an Opencart content management system (CMS) application. Before designing and building this application, the researcher went through collecting data by means of observation, interviews and literature study so that with these data the work was more directed, effective and efficient. After this stage, the researcher conducted a design analysis, namely needs analysis, input analysis and processing analysis in order to obtain an overview of the readiness of the work to be passed. After this process, it is continued with the preparation of category data and product catalogs to be inputted into the system. After completing the construction of this system, it is continued by testing using the blackbox testing method to find out the possibility that there are system functions that are not running. The e-commerce system using the Opencart Content management system (CMS) application is very effective and efficient to use for buying and selling online.